Relationship Between Resistin Levels and Sepsis Among Children Under 12 Years of Age: A Case Control Study - Saboktakin, Lida; Bilan, Nemat; Ghalehgolab Behbahan, Afshin; Poorebrahim, Sadegh (Frontiers in Pediatrics, 2019)
Objective: The aim of this study was to investigate the level of resistin on children with and without sepsis hospitalized in the pediatric intensive care unit (PICU) and compare them to levels in healthy subjects in order to determine the trend of resistin levels in children in PICUs and also to identify the cut-off values for positive sepsis. Methods: This was a case control study conducted in 2014 at children Hospital in Tabriz, Iran. Three groups were investigated, a case group comprised of patients with sepsis admitted to PICU and two control groups; one made up of patients admitted to PICU without sepsis and the other of healthy children. Variables included demographic, anthropometric (growth metric percentile), and clinical factors.Results: Patients were randomized into control group A (n=12, 48%), control group B (n=11, 44%), and the sepsis group (n=24, 47.1%). The difference in the means of resistin levels was significant on the first, fourth, and seventh day (P<0.0001) in the case and control group A. Means comparisons in the case and control group B revealed significant differences on the fourth and seventh day (P=0.005 and P<0.0001 respectively) but not on the first day (P=0.246). The trend of resistin levels increased in the septic group (F Huynh-Feldt=37.83, P<0.0001). The diagnostic accuracy of resistin level was high for discriminating sepsis (area under the receiver operating characteristic curve [AUC] 0.864 [SE =0.41]). The sensitivity was 0.824 and specificity 0.72 with a cut-off point of 5.2 ng/ml on the first day. Conclusion: In the present study, resistin level can be used as an indicator of sepsis in children admitted to PICU. However, the cut-off point based upon when a prediction could be made is different and is dependent on a variety of factors, such as control group and number of days since the first signs of sepsis